2011
DOI: 10.1007/s00508-011-0028-6
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue expression of interleukin-18 mRNA is elevated in subjects with metabolic syndrome and independently associated with fasting glucose

Abstract: Our findings suggest that subjects with MetS have a particular inflammatory pattern in AT, possibly driven by fasting glucose. MDMs might - at least in part - be the cellular source of this increased expression. Together with recent reports, showing IL-18 to be predictive for cardiovascular events, our findings could provide the basis for further research of the role of IL-18 as a link and possible target in the association between MetS and atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…The importance of IL-18 in MetS was also underlined in a review by Trøseid et al [30]. It was also recently shown increased IL-18 mRNA expression in adipose tissue from MetS subjects compared to non-MetS individuals [31]. We could further demonstrate that the influence of the +183 A/G polymorphism was especially apparent in the T2DM and Mets groups, suggesting a beneficial influence of the G-allele in these patients.…”
Section: Discussionsupporting
confidence: 72%
“…The importance of IL-18 in MetS was also underlined in a review by Trøseid et al [30]. It was also recently shown increased IL-18 mRNA expression in adipose tissue from MetS subjects compared to non-MetS individuals [31]. We could further demonstrate that the influence of the +183 A/G polymorphism was especially apparent in the T2DM and Mets groups, suggesting a beneficial influence of the G-allele in these patients.…”
Section: Discussionsupporting
confidence: 72%
“…We observed a significant decrease in leptin levels after euthyroidism was achieved. Study by Yildiz BO et al demonstrated a decrease in leptin levels without a change in fat mass after euthyroidvarious adipokines and inflammatory cytokines involved in atherogenesis, atherothrombosis, and arterial plaque rupture [2,28,29]. Adipocytes express TSH receptors, and VAT proliferation can take place based on TSH expression in visceral and adipose tissue [30].…”
Section: Discussionmentioning
confidence: 95%
“…Such a finding is consistent with the increased adipocytokine release from adipose tissue in obesity (Fain, 2006). Accordingly, fat-resident monocyte/macrophage lineage cells are major sources of circulating IL-18 (Fain, 2006), adipocytes from obese humans secrete 3-fold more IL-18 than those from lean donors (Skurk et al, 2005), and subcutaneous adipose tissue expression of IL-18 is elevated in obesity and metabolic syndrome disorders (Bruun et al, 2007; Leick et al, 2007; Membrez et al, 2009; Weiss et al, 2011). Consistent with a signal of metabolic state, circulating IL-18 levels are increased by hyperglycemia or a high-fat meal (Esposito et al, 2002a; Esposito et al, 2003), and intermittent glucose exposure increases the secretion of IL-18 by adipocytes (Sun et al, 2009).…”
Section: Discussionmentioning
confidence: 99%